Yowamushi pedal. 11 - Watanabe, Wataru, 1971- (Yen Press, 2019)
"Arakita vs Machimiya--who will emerge victorious?! Challenged to an impromptu race where twenty meters decide the difference between winners and losers, Onoda and his hodgepodge "team" struggle to fend off Kureminami's wild beast, Machimiya. The revenge-crazed sprinter is ready to claim victory--until a sudden attack from the sharp-tongued Arakita catches him off guard! Determined to carry Onoda and Manami back to the lead, Hakone's devilish rider won't stop pedaling just yet-not when Fukutomi's orders remain unfulfilled!"--Page [4] of cover.